Emergency medical technician - Barbara Aehlert (McGraw Hill, 2009)
EMTs are often the first licensed EMS personnel to arrive on the scene of an emergency, size up the situation, and provide emergency care and transportation. They practice in a wide diversity of settingsEMTs are everywhere in our community, many of them performing their EMT duties as well as their regular jobs. These providers demonstrate pride and dedication in their role on the frontline of emergency care in this country